Women’s Access to Education in a Patriarchal Society - Delju, Zulaikha; Habibi, Nasima puya (ASEAN Journal of Educational Research and Technology, 2024)
This research study examines women's access to education in Afghanistan, focusing on the challenges faced by women in a patriarchal society. The study aimed to investigate how a male-controlled Afghan society hinders women's access to education and what can be learned from the experiences of women forced to give up on education. A qualitative case study approach is employed, using historical analysis and semi-structured interviews as the main data collection methods. Purposeful sampling is utilized to select participants, specifically older women who have firsthand experience of limited or no access to education. The key findings reveal that factors such as family restrictions, gender-based inequality, poverty, long distances, and societal/cultural norms contribute to women leaving school or never attending. Four provinces in Afghanistan (Kabul, Parwan, Baghlan, and Badakhshan) are represented, with four respondents from each province. The choice of older women is based on their knowledge and insights into the research questions, while the inclusion of participants from remote areas adds to the vulnerability factor. By examining historical evidence and gathering narratives from women who have faced educational barriers, this research seeks to shed light on the extent and impact of women's limited access to education in a patriarchal Afghan society. The findings can contribute to a better understanding of the factors perpetuating gender inequality in education and inform efforts to promote women's educational empowerment in similar contexts.